Campo te Deurle, 4 oktober tot 4 november 1979. - STICHTING MEVROUW JULES DHONDT-DHAENENS (Deurle : Stichting mevrouw J. Dhondt-Dhaenens, 1979)
Apol, Armand ; Battaille, Irène ; Bertrand, Gaston ; Bilquin, Jean ; Wils, Lydia ; Bockstael, Albert ; Brusselmans, Jean ; Cassiman, Jacques ; Cobbaert, Jan ; Delvaux, Paul ; Dero, André ; Driessche, Lucien Van Den ; Evenepoel, Henri ; Frison, Johan ; Georoy ; Van Gindertael, Roger ; Gorus, Pieter ; Guiette, René ; Haine, Désiré ; Haustrate, Gaston ; Jespers, Floris ; De Kat, Anne-Pierre ; Kuppens, Jan ; Lacasse, Joseph ; Lick, Armand Van der ; Lismonde ; Lucas, Jean ; Mara, Pol ; Moers, Karel ; Ost, Alfred ; Paerels, Willem ; Permeke, Constant ; Puvrez, Henri ; Reinhoud ; Roelants, Karel ; Saverijs, Albert ; Servaes, Albert ; Slabbinck, Rik ; De Smet, Gust ; Smolders, Paul ; Somville, Roger ; Spilliaert, Léon ; Tavernier, Armand ; Vaes, Walter ; Verdegem, Jos ; Verheyen, Jef ; Vermeersch, José ; Vermeir, Alfons ; Verpoorten, Oscar ; Wolvens, Henri-Victor
boek